Analysis on the quality of test items on disaster management block - Rosaria Indah; . Mulyadi; Reza Maulana (Syiah Kuala University, 2013)
Written exam is the format most often used to assess the extent of student learning achievement. The advantages of written exam are more easily prepared and relatively more economical when compared with clinical examination test. Block’s written exam, especially on disaster management block is considered important because it will illustrate the students' competence at the end of this special block. This study is a qualitative research, aimed to evaluate the quality of test on disaster management block. The quality of the test were evaluated using qualitative method by deep interviewing 5 criteria of students. The result was analized using Miles and Huberman method and the themes emerged were: 1) The test item in disaster management block were fairly easy 2) Test items were in accordance with the competence of undergraduate, 3) The test item were congruent with the content material taught in this block. However, there were some weaknesses, including: 1) There were repeated items, 2) There were format of question that complicates matters without a clear purpose, 3) There were ‘easy to predict’ item questions, 4) Lack of variation of format. These problems might cause low discriminant items. Recommendation including continues improvement of item developers’ capability by integrate it within curriculum for faculty development programs